Principals and Teachers’ K to 12 Implementation Experiences in Bohol: A Case Study - Fe R. Janiola; Judy Ann O. Ferrater-Gimena; Renato C. Sagayno; Mauro Allan P. Amparado; Rex T. Argate; Rithsun J. Mamacos (Future Science / FSH-PH Publications, 2026)
The K to 12 program was implemented to produce globally-competent graduates by adding two more years of the basic education. However, each implementation of educational reforms would have lots of issues to contend. This study explored the K to12 Senior High School (SHS) Program implementation experiences of the principals and teachers. It employed a case study design, analyzing personal experiences and views to understand and provide insights and recommendations about the K to 12 Basic Education Program (specifically Grade 11), based on the experiences of principals and teachers from Senior High Schools in Bohol, Philippines. Two (2) sets of researcher-designed interview guides were used to conduct unstructured interviews. Thematic analysis was applied in analysing the data.There were three emergent themes that were developed from the experiences of the research participants, such as: K to 12 Transition Management, K to 12 Implementation Challenges, and Mitigating Measures. The essence and salient features of the K to 12 Senior High School (SHS) curriculum were well-crafted and helped the students enhance their skills and prepare them to be globally competitive since the Department of Education crafts it. Although the principals' role was to implement the curriculum and ensure that the students' concerns were addressed and left no one displaced in the Senior High School. Nevertheless, some challenges were encountered, such as the lack of sufficient teaching materials, facilities, classrooms, inadequate teachers' capacity-building programs, and students' social, economic, and psychological struggles that hindered academic access.